2017
DOI: 10.1037/xhp0000325
|View full text |Cite
|
Sign up to set email alerts
|

Domain-general mechanisms for speech segmentation: The role of duration information in language learning.

Abstract: Speech segmentation is supported by multiple sources of information that may either inform language processing specifically, or serve learning more broadly. The Iambic/Trochaic Law (ITL), where increased duration indicates the end of a group and increased emphasis indicates the beginning of a group, has been proposed as a domain-general mechanism that also applies to language. However, language background has been suggested to modulate use of the ITL, meaning that these perceptual grouping preferences may inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…Based on these findings it has been proposed that the use of duration cues for grouping is acquired, while the use of other rhythmic cues for trochaic groupings is innate (more evidence for this proposal comes from studies with rats [73,74] but c.f. [75,76] for evidence that the use of duration for iambic groupings is also innate). The present finding that intensity-based grouping is unmodulated by musical rhythm perception ability is consistent with the assumption of an innate preference for trochaic groupings when intensity alternations are perceived.…”
Section: Dyslexia Rhythmic Grouping Preferences and Musical Rhythm mentioning
confidence: 99%
“…Based on these findings it has been proposed that the use of duration cues for grouping is acquired, while the use of other rhythmic cues for trochaic groupings is innate (more evidence for this proposal comes from studies with rats [73,74] but c.f. [75,76] for evidence that the use of duration for iambic groupings is also innate). The present finding that intensity-based grouping is unmodulated by musical rhythm perception ability is consistent with the assumption of an innate preference for trochaic groupings when intensity alternations are perceived.…”
Section: Dyslexia Rhythmic Grouping Preferences and Musical Rhythm mentioning
confidence: 99%
“…In this instance, recognizing the word you could help the learner to identify the way in which the succeeding ( eat , drink ) and preceding ( yet ) words begin and end, respectively, thus facilitating segmentation. Critically though, some of the speech will remain unsegmented ( biscuityet ), meaning that high-frequency words do not entirely solve the task of speech segmentation—learners must extract the remaining words through further processing, such as computing the transitional probabilities of syllables within words, and inferring word boundaries at points where the subsequent syllable is difficult to predict (e.g., Saffran et al, 1996), or exploiting the broad array of prosodic cues that support segmentation (Curtin, Mintz, & Christiansen, 2005; Frost, Monaghan, & Tatsumi, 2017; Mattys, White, & Melhorn, 2005; Monaghan, White, & Merkx, 2013; Turk & Shattuck-Hufnagel, 2000).…”
mentioning
confidence: 99%
“…This suggestion is supported by recent work showing that durational cues are sufficient to support segmentation of abstract streams of information, such as sequences of patterns. For example, Frost et al (2017) presented adult participants with a stream of visual patterns and found that lengthening the duration of single patterns encouraged participants to perceive a boundary at that position and form a segment from the previously presented patterns. It is therefore conceivable that the CPS reflects bottom-up processing, which can be driven by these lower-level perceptual cues alone.…”
Section: Discussionmentioning
confidence: 99%